Histomorphological structure of the RBCs and WBCs count of the blood picture in diabetic patients for both sexes - Ayad H. Ibraheem; Khulood N. Rasheed (Tikrit Journal of Pure Science, 2023)
Research have been done on patients with diabetes (both types I and II) of the reviewers of medical clinics in the provinces of Erbil and Kirkuk, which included (31) patients of both sexes (16 male, 15 female) aged (20-70 years) to study histomorphological structure of the red blood corpuscle (RBCs) and blood count of the white blood cell (WBCs) count, It was also examined the blood picture of healthy individuals from both sexes for comparison. The results showed the presence of histopathological changes in the red blood corpuscles, like hypochromic with anisopoikilocytosis (different shape and size corpuscles), normochromic crescent shape, hypochromic microcytic cells, mild hypochromic cells anisocytosis and others. The rise significantly in the average number of white blood cells, especially neutrophils and monocytes was detected, significant differences did not appear in the lymphocytes, eosinophil and basophils compared to the number of all kinds of white blood cells in healthy individuals (the control group